2004
DOI: 10.1002/ddr.10351
|View full text |Cite
|
Sign up to set email alerts
|

“Stress‐alleviating” and “vigilance‐enhancing” actions of Ginkgo biloba extract (EGb 761)

Abstract: This overview is focused on the stress-alleviating and vigilance-enhancing properties of Ginkgo biloba extract (EGb 761) that have been observed in animal models and in humans and that appear useful in explaining the therapeutic effects of the extract on non-cognitive brain functions that may be reflective of mood changes. With regard to its stress-alleviating activity, in rodents EGb 761 facilitates behavioral adaptation, decreases circulating levels of corticosterone, catecholamines, ACTH, and CRH, suppresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 87 publications
(111 reference statements)
0
16
0
Order By: Relevance
“…Given the complicated pattern of effects seen on attention task performance, with slowing seen here for 120 mg, but faster performance seen to increase with dose for 240 and 360 mg previously (Kennedy et al, 2000) a potential mechanism that might accommodate complicated behavioural response such as this would be modulation of neurotransmitter synthesis and/or functionality. To this end Ginkgo has been shown to interact with adrenergic, cholinergic, dopaminergic, glutamatergic, serotonergic and GABAergic parameters (for reviews see Ahlemeyer and Krieglstein, 2003;DeFeudis and Drieu, 2004). However, this possibility does not preclude a behavioural influence of any of the wide range of other microscopic cellular effects exerted by Ginkgo or their concordant modulation of physiological parameters.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Given the complicated pattern of effects seen on attention task performance, with slowing seen here for 120 mg, but faster performance seen to increase with dose for 240 and 360 mg previously (Kennedy et al, 2000) a potential mechanism that might accommodate complicated behavioural response such as this would be modulation of neurotransmitter synthesis and/or functionality. To this end Ginkgo has been shown to interact with adrenergic, cholinergic, dopaminergic, glutamatergic, serotonergic and GABAergic parameters (for reviews see Ahlemeyer and Krieglstein, 2003;DeFeudis and Drieu, 2004). However, this possibility does not preclude a behavioural influence of any of the wide range of other microscopic cellular effects exerted by Ginkgo or their concordant modulation of physiological parameters.…”
Section: Discussionmentioning
confidence: 96%
“…and Krieglstein, 2003;Ahmad et al, 2005;DeFeudis and Drieu, 2004;Lee et al, 2004;Shah et al, 2003), beneficial effects on blood circulation (e.g. Ahlemeyer and Krieglstein, 2003;Chung et al, 1999;Jung et al, 1990;Koltringer et al, 1993;Krieglstein et al, 1986;Santos et al, 2003;Topp et al, 2001), with the latter including increased cerebral perfusion in humans (Santos et al, 2003).…”
Section: Introductionmentioning
confidence: 96%
“…In recent years, use of herbal medicine in many countries is widely getting increase. National survey in the U.S.A. revealed that 18% of surveyed adults reported concomitant use of herbal medicines or high-dose vitamins with prescription medications (Feudis and Drieu 2004). Globally, one of the largest selling herbal supplements was standardized extract of Ginkgo leaves, EGB 761 on the markets.…”
Section: Introductionmentioning
confidence: 99%
“…Stress involves a rise in the levels of glucocorticoids, and a subsequent memory dysfunction, increased anxiety, decreased immunity, gastrointestinal tract disturbances, myocardial infarction, or effects such as increased vigilance (Walesiuk and others 2005). Since mood and emotion are related to stress, the alleviating effects of Ginkgo leaf extract may result in improving mood, thus resulting in antidepressant activity (DeFeudis and Drieu 2004).…”
mentioning
confidence: 99%